Unexpected absence of aphasia following left temporal hemorrhage: a case study with functional neuroimaging to characterize the nature of atypical language localization. Issue 1 (2nd January 2021) - Schneck, Sarah M.; Entrup, Jillian L.; Duff, Melissa C.; Wilson, Stephen M.
ABSTRACT: Unexpected absence of aphasia after left-hemisphere perisylvian damage is often assumed to reflect right-hemisphere language lateralization, but other potential explanations include bilateral language representation, or sparing of critical left-hemisphere regions due to individual variability. We describe the case of a left-handed gentleman who presented with no aphasia after a left temporal hemorrhage. We used functional neuroimaging to determine how his language network had been spared. In this case, we observed unequivocal right-hemisphere lateralization of language function, explaining his lack of aphasia. We discuss the variability of language organization and highlight outstanding questions about the implications of damage in different scenarios.